Qualitativ forschen während der Covid-19 Pandemie: Herausforderungen und Chancen der virtuellen Hochschullehre im dualen Studium der Sozialen Arbeit - Franziska Hinßen; Michaela Küppers; Franziska Rieke; Sonja Preissing (IU Internationale Hochschule, 2021)
– The following paper is about the challenges of qualitative research during the Covid-19 pandemic in Bachelor's degree program in Social Work (B.A.) at IU International University of Applied Sciences. Social distancing and lockdown have influenced and affected qualitative research and fieldwork fundamentally. For example, qualitative interviews could not (and still cannot) be conducted in the field without hesitation and concern. This also has an impact on the teaching of qualitative research methods at Universities of Applied Sciences. In the Discussion Paper we look at the changeover from face-to-face teaching to virtual teaching in summer 2020 at the beginning of the Covid-19 pandemic. Here, the question is about the possibilities of virtual teaching and about how to conduct qualitative research in virtual space in the part-time study programme of Social Work at IU International University. In addition to this, the article presents a research project conducted by students in summer 2020 in the lecture of Qualitative Research Methods. The student research group, taking part in the Bachelor's degree program in Social Work (B.A.) at IU International University, conducted qualitative research on the transition from face-to-face teaching to virtual teaching. With the help of qualitative interviews, experiences and specific perspectives of the professor and the students became visible. In the discussion paper, key findings of the research project will be presented. Finally, the role of virtual university teaching in future will be discussed. Here, the challenges as well as opportunities for students and teachers are suggested.
Keywords: 300; Qualitative Sozialforschung; Forschendes Lernen; Covid-19 Pandemie; Digitale Lehre; Duales Studium; Studieren an Hochschulen